The Importance of Disaster Knowledge in Early Childhood for The Future Investment - Widyaningrum, Nrangwesthi; Nurhadiyanti, Arifka Putri; Widana, I Dewa Ketut Kerta (Proceeding International Conference on Science and Engineering, 2020)
Disasters carry consequences for humans and their environment. One of the vulnerabilities to disaster is caused by a lack of knowledge of disasters. Indonesia is a region prone to disasters. This is due to Indonesia’s position which is surrounded by three world tectonic plates and also located in the ring of fire, the most active volcano in the world. According to data from the National Disaster Management Agency (BPNB), during 2018-2019 there have been 3860 natural disaster incidents. The attitude that needs to be raised in minimizing the existence of a disaster is the anticipatory attitude that is accompanied by knowledge to deal with the disaster. Disaster education is one of the directives of the president in disaster management. In line with this directive, it is necessary to transfer disaster knowledge to the community especially to early childhood. Early childhood is a golden period, where the brain develops very quickly and can receive and absorb any good or bad information. For this reason, the purpose of this article is to examine the importance of disaster knowledge for early childhood. This article was compiled using the literature study. Strengthening disaster knowledge about early childhood is the first step towards realizing a disaster-aware society. Disaster aware society will have a better capacity in dealing with disasters so they are capable of threatening disasters around them. Early childhood is one of the future investments and is one of the vulnerable groups to disasters, it is very important to increase disaster knowledge because Indonesia in the future will be led by today’s early generation.